Tracing the Sgr Tails with LPV Carbon Stars. Issue 67 (17th July 2015) - Huxor, A.P.; Grebel, E.K.
Abstract : We use variable AGB carbon stars, in the Catalina Surveys, to probe the tidal arms of the Sgr dSph.